Analisis postur kerja pada aktivitas manintiang menggunakan metode REBA, RULA dan OWAS pada pengolahan emas tradisional tanpa merkuri endapan alluvial Logas, Riau - Sugiono, Nana; Surya, Roberta Zulfhi; Sartika, Laura Dwi Ayu; Atryes, Viola (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Manintiang is a manual activity of separating gold from impurity particles (iron ore, silica, and ilmenite) through gravity, fluid pushing force, and friction force on the surface of the gold panning. Manual activities with an average weight of gold panning, water, and gold concentrate weighing 5–8 kg have the potential to cause musculoskeletal disorders (MSDs) in the short term and cumulative trauma disorders (CTDs) in the long term. This research aims to analyze the work posture of the